Ultrathin GaN quantum disk nanowire LEDs with sub-250 nm electroluminescence. Issue 15 (29th March 2016) - Sarwar, A. T. M. Golam; May, Brelon J.; Chisholm, Matthew F.; Duscher, Gerd J.; Myers, Roberto C.
Abstract : By quantum confining GaN at monolayer thickness with AlN barriers inside of a nanowire, deep ultraviolet LEDs are demonstrated. Abstract : By quantum confining GaN at monolayer thickness with AlN barriers inside of a nanowire, deep ultraviolet LEDs are demonstrated. Full three-dimensional strain dependent energy band simulations are carried out within multiple quantum disk (MQD) GaN/AlN nanowire superlattice heterostructures. It is found that, even within the same nanowire MQD, the emission energy of the ultrathin GaN QDs varies from disk to disk due to the changing strain distribution and polarization charge induced energy band bending along the axial nanowire direction. MQD heterostructures are grown by plasma-assisted molecular beam epitaxy to form self-assembled catalyst-free nanowires with 1 to 2 monolayer thick GaN insertions within an AlN matrix. Photoluminescence peaks are observed at 295 nm and 283 nm from the 2 ML and 1 ML thick MQD samples, respectively. Polarization-doped nanowire LEDs are grown incorporating 1 ML thick GaN MQD active regions from which we observe deep ultraviolet electroluminescence. The shortest LED wavelength peak observed is 240 nm and attributed to electron hole recombination within 1 ML thick GaN QDs.